2022
DOI: 10.1186/s13643-022-01927-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment for pain sensitization in patients with low back pain: protocol for a systematic review

Abstract: Background Low back pain is a disability that occurs worldwide. It is a heterogeneous disorder that affects patients with dominant nociceptive, neuropathic, and central sensitization pain. An important pathophysiology of low back pain involves pain sensitization. Various nonoperative interventions are available for treatment, but there is inconclusive evidence on the effectiveness of these interventions for pain sensitization, leading to arbitrary nonoperative treatments for low back pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…This modality potentially enables less frequent exposure of patients to viral particles, among other things, due to less frequent visits to health care facilities. It is known that this modality of KRT also enables better cardiovascular stability, since it has been shown that patients with DM, HTN, obesity and heart failure with reduced ejection fraction (HFrEF and HFmrEF) represent a group that is at increased risk of death from COVID-19 infection [ 18 ]. Since the representation of patients with DM is up to 70% in the PD population, and cardiovascular comorbidity is present up to 80% [ 11 ], as well as the fact that chronic inflammation and sarcopenia are more common in this group of patients, PD patients are predisposed to more severe forms of infection.…”
Section: Discussionmentioning
confidence: 99%
“…This modality potentially enables less frequent exposure of patients to viral particles, among other things, due to less frequent visits to health care facilities. It is known that this modality of KRT also enables better cardiovascular stability, since it has been shown that patients with DM, HTN, obesity and heart failure with reduced ejection fraction (HFrEF and HFmrEF) represent a group that is at increased risk of death from COVID-19 infection [ 18 ]. Since the representation of patients with DM is up to 70% in the PD population, and cardiovascular comorbidity is present up to 80% [ 11 ], as well as the fact that chronic inflammation and sarcopenia are more common in this group of patients, PD patients are predisposed to more severe forms of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence and incidence rate of LBP is 1.4-20.0% and 0.024-7.0%, respectively 2 . LBP manifests as pain syndrome 3,4 and is an important cause of disability. A systematic analysis of the Global Burden Of Disease Study in 2019 showed that LBP was one of the main causes of disability-adjusted life-years in the 10-24-year age group, and the fourth cause of disability-adjusted life-years in the 25-49-year age group 5 .…”
Section: Introductionmentioning
confidence: 99%